The Influence of the Work Environment and Commitment to Organizational Culture and its Implications on the Performance of Civil Servants - Husniati, Renny; Aratika, Juni; Setiadi, Iwan Kresna (Budapest International Research and Critics University, 2021)
The most important resource of an organization is human resources, so employees are the key determinant of organizational success. Performance is the result of work achieved by an employee in carrying out tasks according to responsibilities. The performance of employees at the Directorate General of Pothan Kemhan is still considered not optimal, it can be seen from the quality of work that has not been in accordance with the expectations of the leadership. The purpose of this study is to prove the influence of the work environment, commitment and organizational culture on employee performance. The research method is a survey method to 141 employees as a representative sample which is calculated based on the Slovin formula, by distributing questionnaires that are answered with a Likekert scale model statement. The analysis technique is path analysis with the help of lisrel software. The results of the analysis can be concluded that the work environment and commitment have a positive and significant effect on organizational culture and also on employee performance. Suggestions are to create a comfortable work environment, increase employee commitment by instilling an attitude of loyalty to the organization, trust in the organization and view that the success of the organization is a success for itself and instill an organizational culture that is good values and beliefs in employees.